Assessment of Health Workers Knowledge toward Occupational Health and Safety Program in Alkut City’s Primary Health Care Centers (Medico Legal Update, 2021)
Health care workers are always exposed to physical, chemical, psychological and biological agents thataffect their health. Regular information is serious for setting priorities necessary to enhance providers, healthand safety, which healthcare facilities like other high danger workplaces are categorized by a high level ofexposure to hazards agents, which significant danger toward health of workers.A descriptive cross sectional study is carried out throughout (1/September/2019 to 1/September/2020) inorder to assess the Health Workers Toward “Occupational Health and safety program” and to find out therelationships between knowledge’s of health workers toward occupational safety and health program andtheir socio-demographic.The study findings indicate that there is a significance relation among health worker’s knowledge aboutoccupational health and safety program with their level of educational and their age. As well as findingsshow that there is a highly significance relation between knowledge about occupation health and safetyprogram with the training of course that health workers participatedin.The study concludes that health workers Age, level education, training course, monthly income, and Numberof years of Employment Have a great effect on occupational health and safety program.The study recommends Encourage health care workers to attend continuing education activities in the formof workshops, conferences, training programs, refreshing courses and review update related to “occupationalhealth and safety program” and ministry of Iraqi health could improve the infections protective processes as“head cap, closed shoes, gloves, and frequent medical examination for communicable diseases” as hepatitis.